Kematangan Beragama Nabi Muhammad Saw (Interkoneksi Hadis Akhlak Nabi Muhammad dengan Ilmu Psikologi Agama) - Mohammad Farah Ubaidillah; Misnawi (STQINIS, 2021)
Prophet Muhammad as the cover of the prophets has a noble character. Behind his moral glory as a prophet, he is also an ordinary human being like other humans. He also feels joy, sadness and other things that are felt by humans. One example that he is the same as other humans, he also made mistakes. The difference between him and other humans is that when he makes a mistake, he immediately gets a warning from Allah. The existence of the nature of basyariyyah in the Prophet Muhammad, made it possible for psychological research to be carried out on him. This study seeks to understand the hadiths about the morals of the Prophet Muhammad with a psychological approach. The purpose of this study is to find out the meaning of the hadith about the morals of the Prophet Muhammad in terms of the perspective of psychology, because so far sometimes the traditions related to the morals of the Prophet Muhammad are understood to be limited to the fiqh dimension.